Informed Consent for Potential Recipients of Pig Kidney Xenotransplantation in the United States. Issue 9 (27th April 2022) - Padilla, Luz A.; Hurst, Daniel; Maxwell, Kathryn; Gawlowicz, Kennan; Paris, Wayne; Cleveland, David; Cooper, David K.C.
Abstract : Clinical trials of kidney xenotransplantation are being considered in the United States. Before this novel procedure can take place, investigators will have to obtain approval from the institutional review board. The consent form that will be used for such a trial and that will receive approval from the institutional review board will be complex. Informed consent—the process by which a research participant provides his/her permission to participate in a clinical trial—is a staple of the research process and most commonly is in the form of a physical document. In the case of a novel procedure with uncertain benefits and risks and a participant population in acute need of a transplant, the consent process is crucial. These complexities may raise several ethical considerations for the initial pig kidney xenotransplantation recipients in the United States that will require adaptations of the required elements of the informed consent process by the US Department of Human and Health Services. The ethical issues include (1) a subject's ability to withdraw from the trial, (2) restrictions on their reproductive rights, and (3) the possibility of the need for quarantine if there is a perceived risk of xenozoonosis. This article aims to discuss ethical considerations that may challenge the general required elements of the informed consent form stipulated by the 45 Code of Federal Regulations 46 of the US Department of Health and Human Services and to suggest recommendations for deliberation.